Topical Clobetasol: An Overlooked Cause of Cushing Syndrome - Ghirardo, Sergio; De Nardi, Laura; Tommasini, Alberto; Barbi, Egidio; Tornese, Gianluca (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background: We describe the case of an 11-year-old boy affected by chronic granulomatous disease complicated by a Crohn’s like colitis needing prolonged treatment with oral corticosteroids. Case Presentation: His therapy for the control of severe oral mucositis was based on topical clobetasol, which did not decrease once the steroids were discontinued. Two years after the oral interruption of the steroids, cushingoid characteristics persisted, the cause of which, after a thorough investigation, was found to be the persistence of the topical clobetasol oral gel. Conclusion: Several studies investigated the efficacy of topical clobetasol for immuno-related mucositis, but little is known about its pharmacokinetics and side effects. In this report, we have reviewed the literature, defining a maximum putative dose of clobetasol mucosal gel to avoid Cushing syndrome.
Keywords: adrenal suppression